Relación entre compromiso organizacional y satisfacción laboral en empresas públicas y privadas - Araujo Gutierrez, Andrea Lucia (2024)
Committed and satisfied employees are crucial for a positive work environment. The connection between organizational commitment and job satisfaction is essential for human resource management; dissatisfaction can lead to stress, anxiety, and an intention to rotate, negatively impacting productivity and performance. The purpose of this study was to understand the relationship between job satisfaction and organizational commitment in employees from both the private and public sectors through an applied review. Ten articles were extracted from academic databases such as Web of Science, APA PsycNET, Proquest, and Scopus, using specific inclusion and exclusion criteria. The results showed a positive and significant relationship between job satisfaction and organizational commitment. Both variables positively influence employee loyalty, turnover trends, and the balance between work and personal life, underscoring the importance of a conducive work environment and strong commitment to contribute to organizational success. In conclusion, job satisfaction and organizational commitment have a positive relationship, which translates into a more satisfying work environment, stimulating a greater willingness to contribute to the success of the company.